0340 Temporal Dynamics Of Non-rapid Eye Movement Sleep In Older Adults With And Without Insomnia. (27th April 2018) - Hogan, S; Delgado, G; Hall, M; Buysse, D; Wilckens, K
Abstract: Introduction: Although sleep in older adults with insomnia may be characterized by reduced slow-wave sleep and increased high frequency EEG activity, studies of NREM EEG do not consistently support this notion. Optimally restorative sleep however, is thought to depend on the temporal dynamics of slow-wave and high frequency activity. Here was accessed overall NREM EEG power differences between older adults with insomnia and control participants with normal sleep across whole-night NREM, individual NREM periods, and within the first NREM period. Methods: Laboratory-based polysomnography was recorded on a single night, following adaptation, in 99 older adults with insomnia and 73 control participants. EEG spectral power was analyzed across all NREM sleep, by individual NREM period, and within the first NREM period (separated by quintiles) in the following frequency bands: slow-oscillation (.5-1 Hz), delta (1–4 Hz), theta (4–8 Hz), alpha (8–12 Hz), sigma (12–16 Hz) and beta (16–20 Hz). Multivariate analyses of variance were used to test effects of group on overall NREM EEG; mixed model analyses were used to test main effects and interactions with group across individual NREM periods and within the five quintiles of the first NREM period. Results: In whole-night NREM, older adults with insomnia had marginally lower slow-oscillation power, no difference in delta power, and higher theta, alpha, sigma and beta power. Group differences were not moderated by NREM period. Within the first NREM period, group differences in slow-oscillation power were significantly moderated by time: The peak in slow-oscillation power at the end of the period was smaller in insomnia vs. control participants. Group differences for all other frequency bands were otherwise stable within the first NREM period. Conclusion: In addition to greater high frequency power in insomnia patients, generation of the slow-oscillation may be diminished, with an altered time course within the first NREM period. These findings may be used to target specific NREM sleep oscillation dynamics that contribute to daytime functions in older adults with insomnia. Support (If Any): National Institute of Health research grants: MH019986, AG020677, and training grant: HL082610.